Hidup Bersama Berbagi Dalam Masyarakat Yang Beragam : Pengalaman Bangsa Amerika Dengan Multikulturalisme - Imam Mahrudi (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2022)
Since at the beginning American society has been heterogenous -- plural society . Under monoculturalism , descriminations were shown as segregation on the public arenas -- in school , bus school transportations , and others. Paradoxically Wasp in individual relation formulated and allowed minority practiced their own cutoms of origin cultural values in individually , groups , in their communities . In work places followed the racist national system of the government . Modern American has been able to imagine , intermingle and learn new social life of the Americanism , also respect , accept , recognize their own identities each other --- intermingle , intermarried with different race and religion . Modern America has shown a high empathic capacity in promoting nationalism , spirit individualism , and democracy. Multiculturalism America respects and accepts other outside environments as plasticity in ability to learn , to change , to adapt to new environment as shown in overcoming the 30's and 70's in economic crises. Multiculturalism strengthen all its institutions due to they are not a white -- finished product , but reflexs ongoing processes as human projects in social policies and social code Ours as Indonesian can learn from American experiences in multiculturalism in respecting and accepting other ethnic identities as we are multicultural able to transform faster to bring our livelihood in social life prosper .